Analysis of the legal preconditions for penal sanction in Paraguay’s legislation (Legal journal - Research in Legal and Social Sciences, 2022)
This paper analyses the condemnability as essential and imperative legal precondition to determine individual accountability from the perspective of criminal law. The main objective of this study is to detail the features of the penal sanction and its development in Paraguayan legislation. In this respect, it can be mentioned that in Paraguay’s current criminal system, the condemnability is a fundamental legal precondition for the imposition of a penal sanction. An individual’s condemnability can be determined based on its capability to comprehend the relevance of the fact and to act accordingly; the individual must also know or must have been able to know his behavior’s unlawfulness, and finally there should be no circumstances that could have prevented or decreased his motivating skill before the norm. In this manner, this paper intends to provide readers a clear and systematic notion of the evolution of the principle of condemnability, which enables to have an overall and precise view of the foundations and the development of this legal figure within criminal system.
Keywords: criminal law; condemnability; criminal accountability; comparative law